Assessing the Fertility Effects of Childcare Cost Subsidies: Evidence from the Child and Dependent Care Tax Credit - Susan L. Averett; Yang Wang (Institute of Labor Economics (IZA), 2023)
We examine the impact of the Child and Dependent Care Tax Credit (CDCTC) on fertility and parental investment in children. The CDCTC aims to support working parents but its availability only to families with children incentivizing having more children or increasing investment in existing ones. Using the Panel Study of Income Dynamics and the National Center for Health Statistics' Natality data, we analyze the effects of state-level CDCTC policies on fertility and birth outcomes. Results indicate that the CDCTC increases labor force participation rates for married mothers, potentially suppressing fertility rates. Additionally, it has a positive effect on gestational age.
Keywords: I38; J13; 330; fertility; birth outcomes; child and dependent care tax credit